The sharing economy - Gossen, Maike; Scholl, Gerd (Ökologisches Wirtschaften - Fachzeitschrift, 2016)
In the so-called sharing economy items are shared, borrowed, exchanged or passed on after use. Scientifically based findings about the users of consumption and business models of this kind are rare. The aim of this article is to add to the available knowledge about the relevance and scope of the sharing economy in Germany.